Diagnostic and therapeutic value of ultrasonography in calcific tendinitis of the rotator cuff: implications for clinical practice - Tuszyńska, Weronika; Wesołowska, Wiktoria; Bachoń, Emilia; Doligalska, Michalina; Stremel, Aleksandra; Komisarczuk, Mateusz; Shyika, Marko (Journal of Education, Health and Sport, 2025)
Introduction: Calcific tendinitis of the rotator cuff is a common musculoskeletal disorder characterized by calcium salt deposits in the tendons of the shoulder’s rotator muscles. Initially asymptomatic, it can cause persistent pain, limited mobility, and a reduced quality of life as the condition progresses. Diagnosis is typically made using clinical evaluation and imaging, with ultrasonography being the preferred non-invasive method, while treatment options range from conservative approaches to advanced ultrasound-guided percutaneous interventions. Aim: The aim of this article is to explain the pathogenesis of calcific tendinitis of the rotator cuff of the shoulder joint and to discuss the use of ultrasound in the diagnosis and treatment of the condition. Review methods: A detailed analysis of recent scientific studies on the treatment and diagnosis of calcific tendinitis of the rotator cuff was conducted. The studies available in PUBMED were analyzed, and the following keywords were used to search for sources: rotator cuff, calcific tendinitis, ultrasonography, percutaneous treatment. Conclusion: Owing to its real-time imaging capabilities and clinical accessibility, ultrasonography plays a central role in both the diagnosis and minimally invasive treatment of calcific tendinitis. The procedure contributes to significant pain relief, improved shoulder function, and faster return to daily activities for affected patients.